ANALYSIS OF THE POTENTIAL OF TUWED VILLAGE AS A SUSTAINABLE CONSERVATION EDUCATIONAL TOURISM IN BALI - Rony Mulia Kusuma Putra; I Ketut Suarta; I Komang Mahayana Putra; Nyoman Mei Rejeki; Solihin Solihin (Journal of Social Entrepreneurship and Creative Technology, 2025)
Community-based sustainable tourism is a strategic approach to destination development that maintains a balance between ecological, socio-cultural, and economic aspects. This study aims to analyze the potential of Tuwed Village in Jembrana Regency, Bali, as a sustainable conservation educational tourism destination. The study used a qualitative approach with a descriptive-exploratory design, using data collection techniques such as field observations, in-depth interviews with village officials, community leaders, and local tourism stakeholders, as well as documentation studies. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that Tuwed Village has significant natural resource potential, including mangrove ecosystems, coastal areas, and organic farming practices that can be developed as a means of environmental education. The socio-cultural aspects of the community, particularly the values ??of local wisdom and traditions of nature conservation, are important assets in the development of community-based educational tourism. From an economic perspective, conservation educational tourism has the potential to create business opportunities and improve community welfare through local economic diversification. Meanwhile, from an institutional perspective, the commitment of the village government and community readiness indicate positive opportunities for strengthening the tourism management structure. This study concludes that Tuwed Village has great potential to be developed as a sustainable conservation educational tourism destination, provided that institutional strengthening, community capacity building, and multi-stakeholder support are provided.